Pengaruh Inovasi Produk dan Citra Merek Terhadap Keputusan Pembelian Skincare Lokal Produk Serum Scarlett Whitening - Rifa Taufiqah; Oktora Yogi Sari (Cakrawala Repositori IMWI, 2023)
This study aims to analyze the effect of product innovation (X1) and brand image (X2) simultaneously and partially on purchasing decisions (Y) for Scarlett Whitening serum products. The sample in this study were 150 consumers who purchased Scarlett Whitening serum products. The sampling technique used in this study was non-probability sampling. The type of non-probability sampling used in this study was purposive sampling. The data analysis method used is multiple linear regression analysis, by going through the stages of the instrument test and the classical assumption test. Testing using the SPSS program version 25 for windows. The results of the study with the F test showed that Product Innovation (X1) and Brand Image (X2) simultaneously had a significant effect on Purchase Decision (Y) for Scarlett Whitening serum products. The results of the t test showed that partially product innovation (X1) and brand image (X2) each had a positive and significant effect on purchasing decisions (Y) for Scarlett Whitening serum products. With a coefficient of determination R Square (R2) of 0.697, which means that the purchase decision variable can be explained by the two independent variables of 69.7% while the remaining 30.3% is explained by other factors not examined in this study.